Analyzing the Components of Emotional Competence of Football Coaches: A Qualitative Study from the Coaches' Perspective - Honggyu Lee; Hagen Wäsche; Darko Jekauc (MDPI AG, 2018)
Emotional Competence (EC) is regarded as a fundamental skill for sports coaches. However, the applications of EC in football coaching are not well understood. This study analyzed the specific emotional processes football coaches experience. We interviewed 18 football coaches and analyzed the interview transcripts by using a systematic analysis process based on Grounded Theory principles. We derived a model from this analysis that comprises a four-phase process: emotional triggers, emotional experiences, emotion regulation strategies, and emotional consequences. In this model, we identified four categories which act as triggers of emotions in football coaches. These emotions can be positive or negative and are manifested at three levels. However, the coaches vary in their capability to perceive emotions. Our model also shows that coaches’ emotion regulation strategies influence the effect of emotional experiences. Experienced emotions promote consequences with psychological and social implications for coaches and may influence their perception of future situations. In short, the process seems to be circular. This finding suggests that the ability to deal with emotions is an important aspect for football coaches.